'The abiding condition was hunger': assessing the long-term biological and health effects of malnutrition and hunger in Canada's residential schools. Issue 2 (September 2017) - Mosby, Ian; Galloway, Tracey
Abstract : Recent studies of residential school survivors and their families focus on the impact of school experiences on the social determinants of health, especially mental health. Less studied is the connection between residential school survivorship and patterns of chronic disease risk among Indigenous peoples in Canada. Narrative accounts, supported by archival records on school food service, provide consistent evidence that children who attended Canada's Indian residential schools experienced chronic undernutrition characterised by insufficient caloric intake, minimal protein and fat, and limited access to fresh produce, often over a period of five to ten years. When examined in the light of literature on the intergenerational effects of twentieth-century famines, this evidence suggests that high prevalence of metabolic risk factors among Indigenous peoples in Canada may be directly associated with the nutritional deprivations experienced by children in residential schools.